Transcriptome-wide characterization and functional analysis of MATE transporters in response to aluminum toxicity in Medicago sativa L. - Xueyang Min; Xiaoyu Jin; Wenxian Liu; Xingyi Wei; Zhengshe Zhang; Boniface Ndayambaza; Yanrong Wang (PeerJ, 2019)
Multidrug and toxic compound extrusion (MATE) transporters contribute to multidrug resistance and play major determinants of aluminum (Al) tolerance in plants. Alfalfa (Medicago sativa L.) is the most extensively cultivated forage crop in the world, yet most alfalfa cultivars are not Al tolerant. The basic knowledge of the MATE transcripts family and the characterisation of specific MATE members involved in alfalfa Al stress remain unclear. In this study, 88 alfalfa MATE (MsMATE) transporters were identified at the whole transcriptome level. Phylogenetic analysis classified them into four subfamilies comprising 11 subgroups. Generally, five kinds of motifs were found in group G1, and most were located at the N-terminus, which might confer these genes with Al detoxification functions. Furthermore, 10 putative Al detoxification-related MsMATE genes were identified and the expression of five genes was significantly increased after Al treatment, indicating that these genes might play important roles in conferring Al tolerance to alfalfa. Considering the limited functional understanding of MATE transcripts in alfalfa, our findings will be valuable for the functional investigation and application of this family in alfalfa.